The effect of residence time on the physical characteristics of PAN-based fibers produced using a solvent-free coagulation process - A. Rahman, M.; Ismail, A. F.; Mustafa, A. (Elsevier, 2007)
The paper reports the fabrication and characterizations of PAN fibers fabricated using residence time in the range of 2–5 s in the solvent-free coagulation process. The PAN fibers were characterized using SEM, FTIR-ATR and tensile testing. The SEM photographs revealed that the cross-section of PAN fiber for all samples were free from large voids. A residence time of 3 s was found to be the most suitable residence time for fabricating the PAN fibers in the solvent-free coagulation bath. FTIR-ATR data suggest that the PAN fibers possessed better molecular orientation and exhibited the highest Young’s modulus of 2.55 GPa.